Synthesis of Robust Water Reuse Networks Using Fuzzy Nonlinear Programming: Mass Exchange-Based Processes - Tan, Raymond Girard R; Cruz, Dennis E (ASEAN Journal of Chemical Engineering, 2005)
Water consumption and effluent generation in industrial plants can be effectively reduced by maximizing utilization of partially contaminated water. A dual approach consisting of graphical pinch methods for targeting followed by the synthesis of water reuse networks using such techniques as mathematical programming is usually employed. Reliable process data is necessary for successful plant retrofitting. In most cases, however, the necessary limiting concentrations and mass loads must be deduced from limited information. It thus becomes necessary to balance the conflicting objectives of minimizing water usage and of ensuring that sufficient stream concentrations fall within their limiting values. The use of fuzzy nonlinear programming for the synthesis of robust water reuse networks is demonstrated using a four-process case study from the literature. Keywords: Fuzzy nonlinear programming, process integration, and water reuse network (WRN).